2001
DOI: 10.1073/pnas.98.3.1124
|View full text |Cite
|
Sign up to set email alerts
|

Expression profiling reveals fundamental biological differences in acute myeloid leukemia with isolated trisomy 8 and normal cytogenetics

Abstract: Acute myeloid leukemia (AML) is a heterogeneous group of diseases. Normal cytogenetics (CN) constitutes the single largest group, while trisomy 8 (؉8) as a sole abnormality is the most frequent trisomy. How trisomy contributes to tumorigenesis is unknown. We used oligonucleotide-based DNA microarrays to study global gene expression in AML؉8 patients with ؉8 as the sole chromosomal abnormality and AML-CN patients. CD34 ؉ cells purified from normal bone marrow (BM) were also analyzed as a representative heteroge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
172
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 260 publications
(185 citation statements)
references
References 51 publications
(41 reference statements)
11
172
0
1
Order By: Relevance
“…2 It is also admitted that the Myc gene located at 8q24 is not a target of þ 8 as Myc in þ 8 AML is down-regulated. 16 Moreover, other data indicated that þ 8 AML showed no specific gene expression signature. 2 In conclusion, our retrospective data show that allo-HSCT is an effective treatment for AML patients harboring þ 8.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 It is also admitted that the Myc gene located at 8q24 is not a target of þ 8 as Myc in þ 8 AML is down-regulated. 16 Moreover, other data indicated that þ 8 AML showed no specific gene expression signature. 2 In conclusion, our retrospective data show that allo-HSCT is an effective treatment for AML patients harboring þ 8.…”
Section: Discussionmentioning
confidence: 99%
“…This study suggested also a worsened outcome for these patients in comparison with other cytogenetic abnormality risk group categories within this heterogeneous 'intermediate' prognosis group. 4 Alternatively, patients with þ 8 occurring concomitantly with other cytogenetic aberrations seem to have the prognosis conferred by the accompanying cytogenetic abnormality, at least in the favorable prognosis group ((t(8;21), t(15;17), inv (16)) or when it is observed concomitantly to additional 11q23 aberrations. 1,5,6 Currently, data assessing specifically the role of allo-hematopoietic SCT (HSCT) in the setting of AML with þ 8 are still relatively sparse.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, drug resistance must be polygenic. The same is likely to be true for the other cancer-specific phenotypes such as grossly altered metabolism, invasiveness, metastasis, and immortality [40,45], because all of these phenotypes correlate with altered expressions of thousands of genes [34,87,[116][117][118] and with highly abnormal concentrations of thousands of normal proteins [16,40,51,119]. Moreover, in highly aneuploid cancer cells the number of centrosomes is increased up to 5-fold -from a normal of two to around ten -and at the same time their structures are often altered [120][121][122][123].…”
Section: Cancers Have Complex Phenotypesmentioning
confidence: 99%
“…Despite the karyotypic instability and heterogeneity of cancer cells partially specific or nonrandom aneuploidies have been found in cancers since in the late 1960s [61,62,[76][77][78][79][80][81][82][83][84][85][86][87]. Since the 1990s, many more nonrandom aneuploidies have been detected in cancers by the use of comparative genomic hybridization, rather than by identifying specific aneusomies cytogenetically [61,[88][89][90][91][92][93][94][95][96].…”
Section: Cancer-specific Aneuploidiesmentioning
confidence: 99%
See 1 more Smart Citation